1999
DOI: 10.2337/diacare.22.9.1462
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitivity indices obtained from oral glucose tolerance testing: comparison with the euglycemic insulin clamp.

Abstract: Previous methods used to derive an index of insulin sensitivity from the OGTT have relied on the ratio of plasma glucose to insulin concentration during the OGTT. Our results demonstrate the limitations of such an approach. We have derived a novel estimate of insulin sensitivity that is simple to calculate and provides a reasonable approximation of whole-body insulin sensitivity from the OGTT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

59
3,956
14
53

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 4,978 publications
(4,082 citation statements)
references
References 0 publications
59
3,956
14
53
Order By: Relevance
“…2B‐E). Furthermore, the insulin sensitivity index (ISI)26 was significantly positively correlated with HIC (Table 4; Fig. 2F).…”
Section: Resultsmentioning
confidence: 92%
“…2B‐E). Furthermore, the insulin sensitivity index (ISI)26 was significantly positively correlated with HIC (Table 4; Fig. 2F).…”
Section: Resultsmentioning
confidence: 92%
“…It was calculated as the change in plasma insulin (PI) from 0 to 30 minutes divided by the change in plasma glucose (PG) over the same period 32. The Matsuda ISI OGTT is an OGTT‐derived measure of whole‐body insulin sensitivity that has been validated against the euglycaemic insulin clamp technique 33. It was calculated using the 75‐g OGTT PG and PI concentrations as follows: √ (fasting PG × fasting PI × mean PG × mean PI), where PG was expressed in mg/dL (1/18 mmol/L) and PI in μU/mL (6 pmol/L).…”
Section: Methodsmentioning
confidence: 99%
“…The insulin sensitivity index (ISI) is based on post–glucose load measures. The ISI reflects whole‐body or peripheral insulin resistance, not only hepatic insulin resistance as reflected by the HOMA‐IR 13. A previous study showed that insulin resistance calculated by post–glucose load measures, but not by fasting insulin, was associated with a risk of incident ischemic stroke 7.…”
Section: Introductionmentioning
confidence: 99%